Edukasi Isi Piringku untuk Pencegahan Obesitas Melalui Instagram dan Facebook - Effendy, Devi Savitri; Muchtar, Febriana; Patricia, Putri; Pratiwi, Rahma Ayu; Fadila, Rahma Resky; Bahar, Hartati; Lestari, Hariati; Tosepu, Ramadhan (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
The rising number of obesity cases among children and adolescents has become a significant public health concern. One contributing factor is the lack of understanding about balanced eating patterns. This community engagement activity aimed to increase public knowledge about the importance of the Isi Piringku (My Plate) concept in preventing obesity, using animated video-based educational media. The educational video was disseminated online through social media platforms Instagram and Facebook. Respondents who accessed the video were asked to complete a post-test and provide feedback via Google Forms. Results showed that out of 117 respondents, the majority stated that the video was easy to understand and improved their knowledge of healthy eating patterns. The highest user interaction was recorded on Instagram, with 190 likes, 69 comments, 11 shares, and 1,500 views. This activity demonstrates that social media can serve as an effective tool for nutrition education, capable of reaching a wide audience efficiently.